Assessing the Knowledge and Awareness Among Selected Tertiary Students in the Accra Metropolis on Zoonotic Infections - Antwi Joseph Barimah; Tweneboah Yvonne Ofosua; Henry Ofosu Addo; Samuella Klenam Agbomadzi; Adom-Brobbey David; Stephen Boakye Agyei; Anin Amoateng Eric (SAGE Publishing, 2023)
Background: Zoonotic infections are a serious threat to human health and a direct risk that could potentially be fatal. Animals both domestic and wild serve as reservoirs for zoonotic infections. Thus, frequent contact with animals might occasionally result in the transfer of infections from animals to people. Ghana is especially susceptible to the effects of zoonotic infections due to the increase in the household human-animal ratio. This study assessed the awareness and knowledge level of tertiary students in a selected tertiary institution on zoonotic infections. Methods: A quantitative research method was employed making use of a descriptive cross-sectional study design. The target population chosen for the research was mainly students from the University of Ghana. A stratified sampling technique was used in selecting participants for the study. 440 participants were selected for the study. The university's four primary colleges served as the strata for the basis of data collection. Results: The study revealed a moderate knowledge level among students. The term "zoonoses" was understood by the majority (70%) of the respondents. Respondents knew at least one route of transmission of zoonotic infection. For the spread of zoonotic infections, close contact with infected animals and consumption of contaminated food were seen as ways of spread by a majority. Conclusion: Although the basic strategies required for the control and elimination of the zoonotic diseases in such tertiary institutions are well known and practiced as per the study findings, zoonoses still persists and this can be attributed to low education on the subject. Knowledge and awareness level on zoonoses especially in tertiary institutions such as the University of Ghana could be improved if relevant authorities create adequate enlightenment programs on improving the knowledge of zoonotic diseases through a variety of media including seminars, workshop, television, radio, newspaper and social media.